Cardiac Gq Receptors and Calcineurin Activation Are Not Required for the Hypertrophic Response to Mechanical Left Ventricular Pressure Overload - Yu, Ze-Yan; Gong, Hutao; Wu, Jianxin; Dai, Yun; Kesteven, Scott H.; Fatkin, Diane; Martinac, Boris; Graham, Robert M.; Feneley, Michael P. (Frontiers in Cell and Developmental Biology, 2021)
Rationale Gq-coupled receptors are thought to play a critical role in the induction of left ventricular hypertrophy (LVH) secondary to pressure overload, although mechano-sensitive channel activation by a variety of mechanisms has also been proposed, and the relative importance of calcineurin- and calmodulin kinase II (CaMKII)-dependent hypertrophic pathways remains controversial. Objective To determine the mechanisms regulating the induction of LVH in response to mechanical pressure overload. Methods and Results Transgenic mice with cardiac-targeted inhibition of Gq-coupled receptors (GqI mice) and their non-transgenic littermates (NTL) were subjected to neurohumoral stimulation (continuous, subcutaneous angiotensin II (AngII) infusion for 14 days) or mechanical pressure overload (transverse aortic arch constriction (TAC) for 21 days) to induce LVH. Candidate signaling pathway activation was examined. As expected, LVH observed in NTL mice with AngII infusion was attenuated in heterozygous (GqI+/–) mice and absent in homozygous (GqI–/–) mice. In contrast, LVH due to TAC was unaltered by either heterozygous or homozygous Gq inhibition. Gene expression of atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP) and α-skeletal actin (α-SA) was increased 48 h after AngII infusion or TAC in NTL mice; in GqI mice, the increases in ANP, BNP and α-SA in response to AngII were completely absent, as expected, but all three increased after TAC. Increased nuclear translocation of nuclear factor of activated T-cells c4 (NFATc4), indicating calcineurin pathway activation, occurred in NTL mice with AngII infusion but not TAC, and was prevented in GqI mice infused with AngII. Nuclear and cytoplasmic CaMKIIδ levels increased in both NTL and GqI mice after TAC but not AngII infusion, with increased cytoplasmic phospho- and total histone deacetylase 4 (HDAC4) and increased nuclear myocyte enhancer factor 2 (MEF2) levels. Conclusion Cardiac Gq receptors and calcineurin activation are required for neurohumorally mediated LVH but not for LVH induced by mechanical pressure overload (TAC). Rather, TAC-induced LVH is associated with activation of the CaMKII-HDAC4-MEF2 pathway.